2015
DOI: 10.2463/mrms.2014-0039
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylaspartate Decrease in Acute Stage of Ischemic Stroke:A Perspective from Experimental and Clinical Studies

Abstract: N-acetylaspartate (NAA) appears in a prominent peak in proton magnetic resonance spectroscopy ( 1 H-MRS) of the brain. Exhibition by NAA of time-dependent attenuation that reflects energy metabolism during the acute stage of cerebral ischemia makes this metabolite a unique biomarker for assessing ischemic stroke. Although magnetic resonance (MR) imaging is a powerful technique for inspecting the pathological changes that occur during ischemic stroke, biomarkers that directly reflect the drastic metabolic chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…NAA can be used as a specific biochemical marker to assess neuronal viability/integrity. The level of Cho in the brain tissue indicates the information about glial cell metabolism [ 35 , 36 ]. In the Stroke group, the NAA/Cr ratio was significantly reduced in the subacute phase (3 – 7 days) after stroke, followed by spontaneous recovery to the normal level on the 14th day after ischemia, while Cho/Cr ratios were obviously increased within 14 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NAA can be used as a specific biochemical marker to assess neuronal viability/integrity. The level of Cho in the brain tissue indicates the information about glial cell metabolism [ 35 , 36 ]. In the Stroke group, the NAA/Cr ratio was significantly reduced in the subacute phase (3 – 7 days) after stroke, followed by spontaneous recovery to the normal level on the 14th day after ischemia, while Cho/Cr ratios were obviously increased within 14 days.…”
Section: Resultsmentioning
confidence: 99%
“…1 H-MRS indicates the information of neuronal/glial metabolism [ 35 , 36 ]. 1 H-MRS of the rat brain was acquired using a PRESS sequence with the following parameters: TR/TE = 1500/135 ms, voxel = 5 cm × 4 cm × 4 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Both NAA and NAAG synthesis in neurons is ATP dependent and hypoxia–ischaemia initiates a decline in NAA/NAAG within hours. Much of the NAA synthesised in the neuron is transported to oligodendrocytes where it is a substrate source for myelin synthesis; it is likely that decreases in NAA following NE will lead to a reduced myelination 14. In adult stroke, NAA levels can predict the fate of an acute ischaemic lesion with more accuracy than DWI 39 40.…”
Section: Discussionmentioning
confidence: 99%
“…A potential benefit of including Thr, in addition to lactate, in the spectral analysis is improvement in the spectral fit in the region around 1.3 ppm in cases where lactate is raised. Similarly, including both NAA and NAA glutamate (NAAG, an abundant neurotransmitter released from axonal terminals with neuronal activity and hydrolysed to NAA and glutamate; NAA+NAAG= total NAA (tNAA)) improves fitting in the region around 2.0 ppm at field strength of 3T 14…”
Section: Introductionmentioning
confidence: 99%
“…The ratio between NAA versus total creatine (NAA/Cre), have been found to be clinically useful, since the latter usually remains constant ( Miller, 1991 ). Most clinical studies using MRS have reported decreases in NAA levels (e.g., ischemia ( Berthet et al, 2014 ), stroke ( Igarashi et al, 2015 ), multiple sclerosis ( Aboul-Enein et al, 2010 ), traumatic brain injury ( Moffett et al, 2013 ). Impairments of energy metabolism decrease NAA levels in the brain.…”
Section: Discussionmentioning
confidence: 99%